2022
DOI: 10.3390/agriculture12101589
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Soil Moisture, Temperature, and Salinity in Cotton Field under Non-Mulched Drip Irrigation in South Xinjiang

Abstract: The mulch film residues in cotton fields in south Xinjiang have caused serious harm to the soil environment and ecological security in the oasis areas. Non-mulched planting provides an alternative approach to this problem. In this experiment, irrigation was provided on the basis of the reference crop evapotranspiration (ET0). Two layouts of drip tapes (1T4R—one tape for four rows; 2T4R—two tapes for four rows) were applied to the non-mulched, drip-irrigated cotton fields in south Xinjiang, and their impacts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Since Yu et al [10] selected and bred the varieties of filmless cotton, filmless cotton has been planted in Southern Xinjiang. Because the soil moisture ecology of filmless cotton was significantly different from that of film-covered cotton (abbreviated as filmed cotton) [11], the effect of the irrigation amount on the root system was quite different. At present, there are many studies on the growth and development, root characteristics and yield formation of cotton with film mulching under the control of irrigation amount, but less on cotton without film mulching [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Since Yu et al [10] selected and bred the varieties of filmless cotton, filmless cotton has been planted in Southern Xinjiang. Because the soil moisture ecology of filmless cotton was significantly different from that of film-covered cotton (abbreviated as filmed cotton) [11], the effect of the irrigation amount on the root system was quite different. At present, there are many studies on the growth and development, root characteristics and yield formation of cotton with film mulching under the control of irrigation amount, but less on cotton without film mulching [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Xinjiang China, is a typical drought and water shortage area 1 , where water resources account for only about 3% of China's total, the agricultural water is seriously lacking, particularly.The sunshine duration in summer is long, so, the evaporation of surface water is large in Xinjiang 2 . The drip irrigation technology has many advantages, such as significant fertilizer saving, yield increasing, efficient water-saving and labor saving 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al showed that drip lines for two rows of plants outperformed drip lines for one row of plants for achieving higher yields and irrigation water efficiency in greenhouse tomato plants [9]. Wang et al reported that soil moisture under two tapes for four rows was greater than that of one tape for four rows, forming a "broad and shallow" wet zone, which was beneficial for the growth of cotton [10]. Drip flow rate is also critical in drip fertigation practice.…”
Section: Introductionmentioning
confidence: 99%